Pharmacy Practice: Exploring the Relationship between SSRIs and Sodium Levels in an Older Adult Population - Sonya L Anderson (INNOVATIONS in Pharmacy, 2016)
I was asked to examine the presence of hyponatremia (<130 mEq/L) in older patients (>65 years) taking Selective Serotonin Reuptake Inhibitors (SSRIs) at Moses Cone Hospital. The presence of hyponatremia in older patients using SSRIs indicates potentially inappropriate use according to the STOPP (Screening Tool of Older Persons’ Potentially Inappropriate Prescriptions) and START (Screening Tool to Alert Doctors to Right Treatment) criteria6. This study was done to assess possible risk factors for potentially inappropriate use of SSRIs by older patients at Moses Cone Hospital. Data collected included the patient’s sex, age, sodium level, and the date the sodium level was drawn. Data also included the specific SSRI and the starting date for the SSRI. The study showed no relationship between age, sex, SSRI prescribed and hyponatremia. However, patients that were prescribed an SSRI for less than a year were more at risk for hyponatremia. Therefore, in order to minimize the risk of hyponatremia, additional monitoring may need to be added at SSRI initiation, three months, six months, and one year, especially in patients with other medications that may lower sodium levels.